KEABSAHAN TANDA TANGAN ELEKTRONIK DALAM AKTA PERNYATAAN KEPUTUSAN RAPAT UMUM PEMEGANG SAHAM MELALUI MEDIA ELEKTRONIK - Putu Angga Pratama; Ida Bagus Rai Djaja (Kertha Negara : Journal Ilmu Hukum, 2013)
Deed statement making general meeting of shareholders is According to Indonesiandictionary, is proof of the deed contains a statement (description, recognition, decision,and so on) about the events that made legal under applicable rules, witnessed. Created andendorsed by officials, the etymological meaning of the word sign is easily found, the mark(signature) in the bottom of things. Something which is meant to act as a sign of approvalof the contents of the deed. For notarial deed, the signature is given by a notary asautensitas a deed, whereas electronic signatures according to Law No. 11 of 2008 is asignature consisting of electronic information attached, associated or linked with otherelectronic information that is used as a tool verification or authentication.